Estudo das propriedades estruturais, ópticas e luminescentes dos vidros PKAl codopados com Dy3+ /Tb3+ para dispositivos de iluminação do estado sólido - BRITO, Kallebe de Oliveira (2025)
In this work, oxyfluorophosphate glasses called PKAl (P2O5-KF-Al2O3), doped with Dy3+ ions and co-doped with Dy3+ and Tb3+ ions, are presented. Sample preparation took place in different phases, which are: synthesis of an unpublished base, individual doping with Dy3+ and Tb3+ ions, and co-doping with both ions. The synthesis took place by the technique melting-quenching. Samples doped individually with Dy2O3 and Tb4O7 both received a fixed concentration of (0.50% mol). For the co-doped samples, the Dy2O3 concentration was set at 0.50% in mol, while the Tb4O7 from 0.25% to 0.75% in mol. Co-doping was performed in order to investigate possible energy transfer between Dy3+/Tb3+ions. Through the results obtained in X-ray diffraction, the amorphous structure of the glasses was confirmed. As a result of the replacement of Al2O3 by Dy3+ and Tb3+ in the doped samples and of P2O5 by Tb4O7 in the co-doped samples, there was an increase in the density and molar volume of the glasses, which indicates a change in the glass structure. The results for refractive index revealed that both doping and co-doping do not contribute significantly to change this property. The FTIR data revealed the characteristic bands of vibrations of the phosphate groups, AlO6 and AlO4. Based on what was exposed by the optical absorption coefficient, the characteristic bands of Dy3+ and Tb3+ ions were identified and it was concluded that the absorption of Tb3+ ions in the co-doped samples obtained a greater intensity due to the increase in its concentration. The excitation spectra provided the most appropriate excitation region for Dy3+ and Tb3+ ions, being located at 350 nm and 376 nm, respectively. By choosing the excitation source, the characteristic emissions of both ions were detected, being 575 nm for Dy3+ and 545 nm for Tb3+. The luminescence spectra of the samples excited at 350, 376 and 405 nm revealed an increase in the emission of specific bands of Tb3+ ions, while for the bands referring to Dy3+ ions there was a decrease. Through the chromaticity diagram of the doped and co-doped samples, the white-green color was verified. The results indicate that the series of PKAl glasses doped and co-doped with Dy3+ and Tb3+ ions are promising candidates for use in the development of solid-state lighting devices.